PSYCHOLOGICAL AND PERSONALITY DISORDERS IN SUICIDE ATTEMPTERS (Journal of Forensic Medicine & Toxicology, 2012)
Attempted suicide is a common clinical problem around the world. Psychiatric disorders are at increased risk for suicide. 100 consecutive cases of first suicide attempters were selected. Risk-Rescue rating was applied in suicide attempters to know the medical seriousness of the suicide attempt. Structured clinical interview (MINI Plus) and semi-structured clinical interview (IPDE) were used for diagnosis. These subjects had significantly more number of patients with family history of psychiatric illnesses (27%). Interpersonal problems with a significant person (46%) were the most frequent reason attributed by the suicide attempters. Suicide attempters had significantly more undesirable and ambiguous life events compared to the controls. Those who made serious suicide attempt had significantly more undesirable life events in the past six months. Most common diagnostic categories were mood disorders, adjustment disorders and substance related disorders. Insecticides and pesticides were the most common agents (71%) employed to attempt suicide. The overall medical seriousness of the suicide attempt was of moderate lethality.
Keywords: Psychiatric disorders; Personality disorders; Stressful events; Comorbidity; Attempted suicide